The Effects of Human Resource Capability and Internal Customer Satisfaction on Organizational Effectiveness. (7th July 2015) - Chuang, Huan-Ming; Liu, Mao-Jen; Chen, You-Shyang
Human resource capability is valuable, rare, irreplaceable, and difficult to imitate; therefore, it is crucial for creating sustainable competitive advantages. Human resource capability can be appropriately used to improve the performance of an organization. This study adopted a process perspective to propose an integrated model that comprehensively considers the key variables of human resource capability and organizational effectiveness. In addition, empirical research was conducted by using a state-owned Company-A as an example. The theory of service-profit chain posits that internal customer satisfaction and loyalty influences customer satisfaction and loyalty before affecting a company's profitability and growth. Consequently, we explore the effects of human resource capability, internal customer satisfaction and commitment, and organizational effectiveness. Based on research findings, insightful and practical guidance is suggested for leveraging human resource capability to enhance organizational performance.